2017
DOI: 10.7554/elife.28611
|View full text |Cite
|
Sign up to set email alerts
|

Phasic and tonic neuron ensemble codes for stimulus-environment conjunctions in the lateral entorhinal cortex

Abstract: The lateral entorhinal cortex (LEC) is thought to bind sensory events with the environment where they took place. To compare the relative influence of transient events and temporally stable environmental stimuli on the firing of LEC cells, we recorded neuron spiking patterns in the region during blocks of a trace eyeblink conditioning paradigm performed in two environments and with different conditioning stimuli. Firing rates of some neurons were phasically selective for conditioned stimuli in a way that depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 35 publications
7
40
0
Order By: Relevance
“…MTL does not directly control behavioral responses, since conditioning‐specific responses predated the appearance of conditioned responses, and were essentially identical on CR and no‐CR trials after learning (Figure ), suggesting that these regions mediate temporal associations rather than motor outputs. Our observations converge with those of Pilkiw et al (), who observed that lateral entorhinal cortex firing patterns of individual neurons were not correlated with the expression of conditioned eyeblinks on a trial‐by‐trial basis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…MTL does not directly control behavioral responses, since conditioning‐specific responses predated the appearance of conditioned responses, and were essentially identical on CR and no‐CR trials after learning (Figure ), suggesting that these regions mediate temporal associations rather than motor outputs. Our observations converge with those of Pilkiw et al (), who observed that lateral entorhinal cortex firing patterns of individual neurons were not correlated with the expression of conditioned eyeblinks on a trial‐by‐trial basis.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that our rabbits were head restrained and not moving through the environment likely minimized spatial information flowing through the MTL and accentuated the processing of stimulus associations that would otherwise occur when freely moving animals stop and attend to conditioning stimuli (Shan, Lubenov, Papadopoulou, & Siapas, ). In contrast, the context dependent environment that is sometimes used by the Takehara–Nishiuchi laboratory revealed that context can and does affect MTL neuronal responses during EBC experiments in freely moving rats with some lateral entorhinal neurons responding to stimuli in one environment and not another (Pilkiw et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, sustained responses have been observed in both in-vitro [33][34][35][36] and anesthetized 37,38 approaches. Similarly, slow changes in firing rate were observed in the EC of rats during trace eyeblink conditioning across distinct environmental contexts 39 . Computational modeling studies have suggested that properties of calcium non-specific cation current observed in slice are sufficient to generate a spectrum of response decay periods, ranging from brief to prolonged 40,41 .…”
Section: Discussionmentioning
confidence: 88%
“…However, neurons and networks in LEC code beyond this by incorporating representations of context, because LEC is critically involved in complex object‐context associations binding together information relating to objects, places, and contexts (Scaplen, Ramesh, Nadvar, Ahmed, & Burwell, ; Wilson et al, ; Wilson, Watanabe, Milner, & Ainge, ). Recent electrophysiological studies provide data suggesting that distinct contextual features of experiences are represented in LEC both at the single‐cell and population level (Pilkiw et al, ; Tsao et al, ). Further analysis of LEC ensemble activity indicated a shift of population states according to the temporal progression of the experimental event.…”
Section: Introductionmentioning
confidence: 99%